A method of preparing a composite biological patch

CN117754891BActive Publication Date: 2026-10-20YANTAI ZHENGHAI BIO TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311854239.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2026-10-20
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

目前制备纤维增强海绵复合肩袖补片的常规方法是流延工艺,但是这些常规方法存在的一个技术难点是:如何将纤维层和海绵基质层结合紧密,从而可以减少产品的缺陷,保证其具备较高的机械强度,另外,在制备纤维增强海绵复合肩袖补片时,多层纤维层的存在可以有效提高补片的强度性能,但是现有的工艺无法实现多层纤维层的使用,因为多层纤维层的实质会导致纤维层和海绵基质层的结合性差,最终无法得到合格的生物补片

Benefits of technology

[0028]本发明所述的复合生物补片具有纤维增强的海绵结构,在有利于组织细胞长入的同时具有较高的机械强度,可用于组织的修复、重建和机械增强。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117754891B_ABST
    Figure CN117754891B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of tissue repair, in particular to a preparation method of a composite biological patch, which comprises the following steps: sequentially laying a fiber layer, a release cloth and a flow guide net in a mold from bottom to top, sealing a bag and the mold to form a sealed mold system, and the fiber layer, the release cloth and the flow guide net are located in the sealed mold system; connecting a flow guide pipe and a vacuum pipe to the sealed mold system; using a vacuum pump to draw a vacuum in the sealed mold system and keep a negative pressure state, automatically injecting a matrix layer slurry into the sealed mold system through the flow guide pipe, closing the flow guide pipe after the matrix layer slurry fills the whole sealed mold system, and closing the vacuum pump; demolding after freezing the mold system to obtain a fiber-reinforced composite matrix, and obtaining the composite biological patch after freeze-drying. The preparation method can make the matrix layer and the fiber layer more closely combined, thereby ensuring the mechanical strength of the product; in addition, the preparation method can realize the combination of multiple layers of fibers and the matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a composite biological patch, belonging to the field of tissue repair technology. Background Technology

[0002] Rotator cuff tears are a common cause of shoulder pain, reduced range of motion, and weakened function. While rotator cuff repair surgery has advanced rapidly, the failure rate for repairing large-area rotator cuff tears remains high. Addressing the limitations of traditional surgical methods, arthroscopic arthroscopic repair or bridging repair using rotator cuff patches has emerged as a new option.

[0003] Rotator cuff patches need to possess good biocompatibility to promote the healing of damaged rotator cuff tissue, improve the success rate of surgical repair, and enhance postoperative function. Simultaneously, rotator cuff patches must have sufficient mechanical strength to ensure adequate mechanical support during the healing process. Therefore, designing rotator cuff patches with excellent mechanical strength and good biocompatibility is of significant value for the clinical repair of rotator cuff injuries.

[0004] Fiber-reinforced sponge composite rotator cuff patches possess both advantages mentioned above. The fiber structure ensures the patch's mechanical strength and support, while the three-dimensional porous structure of the biomaterial-based sponge guarantees biocompatibility and provides porosity suitable for tissue growth. Currently, the conventional method for preparing fiber-reinforced sponge composite rotator cuff patches is the casting process. However, a key technical challenge with these methods is achieving a tight bond between the fiber layer and the sponge matrix layer to minimize defects and ensure high mechanical strength. Furthermore, while multiple fiber layers can effectively improve the patch's strength, current processes cannot utilize them effectively because they inherently lead to poor bonding between the fiber layer and the sponge matrix layer, ultimately resulting in substandard biocompatible patches. Therefore, there is an urgent need to develop a new manufacturing process for fiber-reinforced sponge composite rotator cuff patches. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing a composite biological patch. The prepared composite biological patch exhibits good biocompatibility and mechanical strength, and the preparation method is simple and easy to operate.

[0006] The technical solution of this invention to solve the above-mentioned technical problems is as follows: A method for preparing a composite biological patch, wherein the preparation method is as follows:

[0007] S1. The fiber layer, release cloth, and flow guide net are laid flat in the mold from bottom to top, and the sealing bag and the mold form a sealed mold system, with the fiber layer, release cloth, and flow guide net located within the sealed mold system; the sealed mold system is connected to a flow guide tube and a vacuum tube;

[0008] S2. Use a vacuum pump to evacuate the sealing mold system and maintain a negative pressure state. Automatically inject the matrix layer slurry into the sealing mold system through the guide pipe. After the matrix layer slurry fills the entire sealing mold system, close the guide pipe and turn off the vacuum pump.

[0009] S3. After freezing the mold system, demold to obtain a fiber-reinforced composite matrix, and freeze-dry to obtain a composite biological patch.

[0010] Furthermore, the fiber layer is a woven structure membrane material, an electrospun structure membrane material, or a similar or dissimilar decellularized dermal matrix membrane material.

[0011] In the composite biological patch, the number of fiber layers is one or more.

[0012] Furthermore, the material of the woven structure membrane is selected from at least one of polypropylene, ultra-high molecular weight polyethylene, polylactic acid, polycaprolactone, and polyethylene terephthalate.

[0013] The electrospun structural membrane material is a fiber structure formed by electrospinning technology using at least one of polylactic acid, polycaprolactone, collagen, silk fibroin, chitosan, and polyglycolic acid.

[0014] Furthermore, the matrix layer slurry is at least one of collagen solution, silk fibroin solution, gelatin solution, and decellularized dermal matrix microfiber solution.

[0015] Furthermore, the collagen solution, silk fibroin solution, and gelatin solution are prepared by dissolving collagen, silk fibroin, and gelatin respectively in water or an aqueous acetic acid solution;

[0016] The method for preparing the decellularized dermal matrix microfiber solution is as follows: the decellularized dermal matrix collagen membrane is soaked in an aqueous acetic acid solution, the soaked collagen membrane is mixed with water and mechanically broken to obtain microfibers, which are then filtered through a 200-400 mesh sieve to obtain the decellularized dermal matrix microfiber solution.

[0017] Furthermore, the mass fraction of acetic acid in the acetic acid aqueous solution is 0.05% to 2.0%;

[0018] The mass fraction of solute in the matrix layer slurry is 0.1% to 5.0%.

[0019] Preferably, the mass fraction of solute in the matrix layer slurry is 0.5% to 2.0%.

[0020] Furthermore, the viscosity of the matrix layer slurry is 1000 to 7000 centipoise, and the pressure of the vacuum pump is -0.095 to -0.05 MPa;

[0021] The viscosity of the matrix layer slurry is A, in centipoise; the pressure of the vacuum pump is P, in MPa; P = p ± 0.001, p = -(0.006A + 50) * 0.001.

[0022] Furthermore, the freezing temperature is -50℃ to -1℃, and the freezing time is 8 to 48 hours;

[0023] The freeze-drying temperature is -50℃ to -80℃, and the freeze-drying time is 24 to 72 hours.

[0024] Furthermore, the freezing temperature is -30℃ to -1℃, and the freezing time is 16 to 30 hours;

[0025] The freeze-drying temperature is -65℃ to -80℃, and the freeze-drying time is 30 to 60 hours.

[0026] Furthermore, the freezing temperature is a gradient cooling method, and the freezing process is -1 to -2℃ for 1 to 5 hours; -3 to -15℃ for 2 to 15 hours; -16 to -50℃ for 5 to 28 hours.

[0027] The beneficial effects of this invention are:

[0028] The composite biological patch of the present invention has a fiber-reinforced sponge structure, which facilitates the ingrowth of tissue cells while having high mechanical strength, and can be used for tissue repair, reconstruction and mechanical enhancement.

[0029] The vacuum method described in this invention uses a vacuum infusion process instead of a conventional casting process, which can completely eliminate the gas in the system. This prevents a large number of air bubbles from remaining during the bonding process between the matrix slurry and the fiber layer, and also ensures a tight bond between the fiber layer and the matrix. This reduces defects in the resulting product and guarantees high mechanical strength. Furthermore, it ensures the smooth infusion of high-viscosity matrix slurry and maintains a smooth surface. More importantly, the vacuum infusion process enables the bonding of multiple layers of fiber to the matrix, resulting in a higher-strength biological patch, thus meeting the high-strength and diverse requirements of such patches in areas such as tendons and ligaments. Attached Figure Description

[0030] Figure 1 This is a schematic diagram illustrating the principle of the composite biological patch preparation method described in this invention.

[0031] Figure 2 Example 2: Comparison of cell proliferation rate data between composite biological patch and PET fiber patch;

[0032] Figure 3 A schematic diagram illustrating the establishment of a rotator cuff injury model;

[0033] Figure 4Images of bridging and repairing tendon injuries;

[0034] Figure 5 Images taken 2 months after bridging repair surgery;

[0035] In the diagram, 1. Matrix slurry; 2. Guide pipe; 3. Mold; 4. Sealing bag; 5. Fiber layer; 6. Release cloth; 7. Guide net; 8. Sealant; 9. Vacuum tube; 10. Vacuum pump. Detailed Implementation

[0036] The specific embodiments of the present invention will be described in detail below. The present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used is for describing particular embodiments only and is not intended to limit the invention.

[0038] A method for preparing a composite biological patch, wherein the preparation method is as follows:

[0039] S1, such as Figure 1 As shown, the fiber layer 5, the release cloth 6, and the flow guide net 7 are laid flat in the mold 3 from bottom to top. The sealing bag 4 and the mold 3 form a sealed mold system, and the fiber layer 5, the release cloth 6, and the flow guide net 7 are located within the sealed mold system. The sealed mold system is connected to the flow guide pipe 2 and the vacuum pipe 9.

[0040] S2. Use vacuum pump 10 to evacuate the sealing mold system and maintain a negative pressure state. Automatically inject matrix layer slurry 1 into the sealing mold system through guide pipe 2. After the matrix layer slurry 1 fills the entire sealing mold system, close guide pipe 2 and turn off vacuum pump 10.

[0041] S3. After freezing the mold system, demold to obtain a fiber-reinforced composite matrix, and freeze-dry to obtain a composite biological patch.

[0042] More specifically, in this embodiment of the invention, the mold 3 is a stainless steel mold, and the sealed bag 4 and the mold 3 are reinforced by sealant 8 to form a sealed mold system.

[0043] Specifically, the fiber layer is a woven structure membrane material, an electrospun structure membrane material, or a decellularized dermal matrix membrane material of the same or different species; in the composite biological patch, the fiber layer has one or more layers.

[0044] Specifically, the material of the woven structure membrane is selected from at least one of polypropylene, ultra-high molecular weight polyethylene, polylactic acid, polycaprolactone, and polyethylene terephthalate;

[0045] The electrospun structural membrane material is a fiber structure formed by electrospinning technology using at least one of polylactic acid, polycaprolactone, collagen, silk fibroin, chitosan, and polyglycolic acid.

[0046] Specifically, the matrix layer slurry is at least one of collagen solution, silk fibroin solution, gelatin solution, and decellularized dermal matrix microfiber solution.

[0047] Specifically, the collagen solution, silk fibroin solution, and gelatin solution are prepared by dissolving collagen, silk fibroin, and gelatin in water or an aqueous acetic acid solution, respectively.

[0048] The method for preparing the decellularized dermal matrix microfiber solution is as follows: the decellularized dermal matrix collagen membrane is soaked in an aqueous acetic acid solution, the soaked collagen membrane is mixed with water and mechanically broken to obtain microfibers, which are then filtered through a 200-400 mesh sieve to obtain the decellularized dermal matrix microfiber solution.

[0049] Specifically, the acetic acid aqueous solution contains 0.05% to 2.0% acetic acid by mass; the matrix slurry contains 0.1% to 5.0% solute by mass.

[0050] Preferably, the mass fraction of solute in the matrix layer slurry is 0.5% to 2.0%.

[0051] Specifically, the viscosity of the matrix layer slurry is 1000 to 7000 centipoise, and the vacuum pump pressure is -0.095 to -0.05 MPa;

[0052] The viscosity of the matrix layer slurry is A, in centipoise; the pressure of the vacuum pump is P, in MPa.

[0053] P=p±0.001, p=-(0.006A+50)*0.001.

[0054] Specifically, the freezing temperature is -50℃ to -1℃, and the freezing time is 8 to 48 hours; the freeze-drying temperature is -50℃ to -80℃, and the freeze-drying time is 24 to 72 hours.

[0055] Preferably, the freezing temperature is -30℃ to -1℃ and the freezing time is 16 to 30 hours; the freeze-drying temperature is -65℃ to -80℃ and the freeze-drying time is 30 to 60 hours.

[0056] Specifically, the freezing temperature can be a gradient cooling method, and the freezing process is -1 to -2℃ for 1 to 5 hours; -3 to -15℃ for 2 to 15 hours; -16 to -50℃ for 5 to 28 hours.

[0057] Example 1

[0058] (1) Preparation of decellularized dermal matrix microfiber solution:

[0059] Bovine decellularized dermal matrix collagen membrane material was obtained by conventionally degreasing and decellularizing bovine dermal layers through a series of steps. Then, 2g of the bovine decellularized dermal matrix collagen membrane material was soaked in 50mL of 0.1% acetic acid aqueous solution for 1 hour. After removing the bovine decellularized dermal matrix collagen membrane material and draining off the solution floating on its surface, the material was mixed with 100mL of deionized water and crushed in a crusher until it reached a solution state. The solution was then filtered through a 300-mesh sieve to obtain a decellularized dermal matrix microfiber solution with a viscosity of 6500 centipoise.

[0060] (2) Preparation of composite biological patch:

[0061] Two pieces of bovine decellularized dermal matrix membrane, a release cloth, and a flow guide net are laid flat inside a stainless steel mold from bottom to top. The flow guide tube is installed, and the mold is sealed with a sealing bag. A vacuum pump is used to evacuate the sealed mold system to a pressure of -0.09 MPa. The decellularized dermal matrix microfiber solution is automatically injected into the sealed mold system through the flow guide tube. After the slurry has filled the entire sealed mold system, the flow guide tube is closed, and the vacuum pump is turned off.

[0062] The sealing mold system was frozen at -2℃ for 2 hours, at -10℃ for 5 hours, and at -20℃ for 15 hours. The frozen sealing mold system was demolded, and the sealing bag, demolding cloth, and flow guide net were removed. Only the frozen slurry and fiber layer composite were freeze-dried at -67℃ for 30 hours to obtain the composite biological patch.

[0063] Example 2

[0064] (1) Preparation of collagen solution:

[0065] Collagen was extracted from bovine Achilles tendon using an enzymatic hydrolysis method. Fresh bovine Achilles tendons were washed, and the tendon membrane, fat, and muscle were removed. The tendons were then cut into small pieces and soaked in a 10% sodium chloride solution for 24 hours. Next, they were defatted by soaking in a 1:1 mixture of ethanol and isopropanol at 4°C. After defatting, the tendons were washed, the pH was adjusted to 2-3, and pepsin was added. The mixture was reacted at room temperature for 72 hours. The supernatant was collected by centrifugation, purified by salting out and dialysis, and then freeze-dried to obtain solid collagen. 1.5 g of collagen was weighed and dissolved in 100 mL of a 0.5% acetic acid aqueous solution. The solution was magnetically stirred for 2 hours to obtain a matrix layer collagen solution. The viscosity of the collagen solution was measured to be 3500 centipoise.

[0066] (2) Preparation of composite biological patch:

[0067] Two commercially available polyethylene terephthalate (PET) fiber patches (National Medical Device Registration Certificate 20173130332), a release cloth, and a flow guide net were laid flat in a stainless steel mold from bottom to top. The flow guide tube was installed, and the mold was sealed with a sealing bag. A vacuum pump was used to evacuate the sealed mold system to a pressure of -0.07 MPa. Collagen solution was automatically injected into the sealed mold system through the flow guide tube. After the slurry filled the entire sealed mold system, the flow guide tube was closed and the vacuum pump was turned off. The sealed mold system was frozen at -20℃ for 24 hours. The frozen sealed mold system was demolded, and the sealing bag, release cloth, and flow guide net were removed. Only the frozen slurry and fiber layer composite were freeze-dried at -67℃ for 48 hours to obtain a composite bio-patch of collagen sponge and PET fiber.

[0068] Example 3

[0069] (1) Preparation of gelatin solution

[0070] Weigh 3g of gelatin granules and 100mL of deionized water, and stir in a 60℃ constant temperature water bath for 4h to obtain a gelatin aqueous solution for the matrix layer slurry with a viscosity of 1500 centipoise.

[0071] (2) Preparation of composite biological patch:

[0072] Two commercially available polyethylene terephthalate (PET) fiber patches (National Medical Device Registration Certificate No. 20173130332), a release cloth, and a flow guide net were laid flat in a stainless steel mold from bottom to top. The flow guide tube was installed, and the mold was sealed with a sealing bag. A vacuum pump was used to evacuate the sealed mold system to a pressure of -0.06 MPa. The matrix layer slurry gelatin aqueous solution was automatically injected into the sealed mold system through the flow guide tube. After the slurry filled the entire sealed mold system, the flow guide tube was closed and the vacuum pump was turned off. The sealed mold system was frozen at -20℃ for 24 hours. The frozen sealed mold system was demolded, and the sealing bag, release cloth, and flow guide net were removed. Only the frozen slurry and fiber layer composite were freeze-dried at -67℃ for 48 hours to obtain a composite bio-patch of collagen sponge and PET fiber.

[0073] Comparative Example 1

[0074] The composite biological patch was prepared using the same raw materials as in Example 1, except that: Comparative Example 1 used a conventional casting method to prepare the composite biological patch, the specific process of which is as follows:

[0075] Two bovine decellularized dermal matrix membranes from Example 1 were overlapped and laid flat in a freeze-drying mold. The slurry obtained in Example 1 was poured into the freeze-drying mold, and the mold was gently shaken. After the slurry flowed and covered the entire mold, the mold system was frozen at -2°C for 2 hours, at -10°C for 5 hours, at -20°C for 15 hours, and then freeze-dried at -67°C for 30 hours to obtain the composite biological patch.

[0076] Comparative Example 2

[0077] The composite biological patch was prepared using the same raw materials as in Example 1, except that the vacuum pump pressure in Comparative Example 2 was -0.05 MPa, and the other process parameters were exactly the same as in Example 1.

[0078] Performance testing:

[0079] I. Peel Strength Performance Test

[0080] Five locations at the same site of the composite bio-patterns obtained in the above examples and comparative examples were selected, and the thickness at the five locations was measured using a thickness gauge. The measurement results are shown in Table 1. The peel strength between the two fiber layers in the composite bio-patterns of Examples 1-3 and Comparative Examples 1-2 was tested using a universal testing machine (to reduce measurement error, five samples were tested for each composite bio-pattern of each example or comparative example), and the measurement results are shown in Table 2.

[0081] Table 1. Measurement results of composite biological patch thickness

[0082]

[0083]

[0084] Table 2. Test results of peel strength (MPa) of composite biological patch

[0085]

[0086] As can be seen from the data in Tables 1 and 2, the composite biological patches prepared by the preparation method described in this invention in Examples 1-3 have a more uniform thickness and a greater peel strength of the fiber layer, thus the fiber structure and the sponge structure are more tightly bonded.

[0087] A comparison of the experimental data from Example 1 and Comparative Example 1 shows that the composite biological patch obtained by the vacuum infusion method described in this invention exhibits significantly higher thickness uniformity than that obtained by the conventional casting method. Furthermore, the fiber layer exhibits greater peel strength, and the fiber structure is more tightly integrated with the sponge structure. In addition, practical experience reveals that the preparation method described in this invention is simpler to operate, requires less time, and significantly reduces human error, thereby improving the product yield.

[0088] A comparison of the experimental data from Example 1 and Comparative Example 2 shows that the composite biological patch prepared by using a vacuum infusion process with an appropriate vacuum degree based on the slurry viscosity has a more uniform thickness. Maintaining a reasonable vacuum degree in the mold during the infusion process can avoid introducing a large number of air bubbles during the infusion process, resulting in fewer defects in the porous sponge structure and a more compact structure. At the same time, the fiber structure and sponge structure are more tightly combined, which is more conducive to maintaining the spatial structure of the patch, thereby ensuring the repair, reconstruction and mechanical reinforcement of rotator cuff injuries.

[0089] II. Tensile Strength Test

[0090] The tensile strength of the composite biological patch obtained in Example 1 and the bovine decellularized dermal matrix membrane used for the fiber layer were tested using a universal testing machine. The measurement results are shown in Table 3.

[0091] Table 3 Tensile strength (MPa) test results

[0092]

[0093] As can be seen from Table 3, the production process of bovine decellularized dermal matrix membrane is affected by the source of materials and the production process, and the thickness of the membrane material is limited, which results in limited mechanical strength of the material. The preparation method provided by the present invention can realize the composite of multilayer bovine decellularized dermal matrix membrane and matrix, thereby improving the mechanical strength of the composite patch.

[0094] III. Cell Proliferation Rate Test

[0095] Cell proliferation rate study: Using human fibroblasts (MRC5) as a model, the cell proliferation of the composite biological patch and PET fiber patch (National Medical Device Registration Certificate 20173130332) in Example 2 was detected by MTT assay, and the cell proliferation rate was tested after 48h and 72h of culture. The test results are as follows. Figure 2 The cell proliferation rate of the composite biological patch was significantly better than that of the PET fiber patch, indicating that the composite biological patch has better biocompatibility. Compared with the single PET fiber patch, the sponge structure of the composite biological patch prepared by the vacuum perfusion process has porosity, which is conducive to cell adhesion, migration and ingrowth of new tissue in local repair.

[0096] IV. Animal Experiments

[0097] New Zealand white rabbits were given general anesthesia, and a longitudinal skin incision of approximately 3 cm was made at the shoulder joint. The deltoid muscle was bluntly dissected to expose the insertion of the supraspinatus tendon on the greater tubercle. The supraspinatus tendon was then sharply severed, and a 0.3 cm × 0.3 cm section of tendon tissue was removed to create a rotator cuff injury model (e.g., Figure 3 The composite biological patch obtained in Example 1 was cut to a length of 0.5 cm and a width of 0.3 cm for bridging and repairing tendon injuries. During tendon repair, one end of the patch was sutured to the tendon stump, and the other end was fixed to the bone surface (e.g., Figure 4 Anatomical observation two months after bridging repair surgery revealed an orderly arrangement of regenerated collagen fibers, an increased overall number of tendon cells, and a higher degree of tendon maturity (e.g., Figure 5 ).

[0098] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0099] For those skilled in the art, various modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A method for preparing a composite biological patch, characterized in that, The preparation method is as follows: S1. The fiber layer, release cloth, and flow guide net are laid flat in the mold from bottom to top, and the sealing bag and the mold form a sealed mold system, with the fiber layer, release cloth, and flow guide net located within the sealed mold system; the sealed mold system is connected to a flow guide tube and a vacuum tube; S2. Use a vacuum pump to evacuate the sealing mold system and maintain a negative pressure state. Automatically inject the matrix layer slurry into the sealing mold system through the guide pipe. After the matrix layer slurry fills the entire sealing mold system, close the guide pipe and turn off the vacuum pump. S3. After freezing the mold system, demold to obtain a fiber-reinforced composite matrix, and freeze-dry to obtain a composite biological patch; The viscosity of the matrix layer slurry is 1000~7000 centipoise, and the pressure of the vacuum pump is -0.095~-0.05 MPa; The viscosity of the matrix layer slurry is A, in centipoise; the pressure of the vacuum pump is P, in MPa; P = p ± 0.001, p = -(0.006A + 50) × 0.

001.

2. The method for preparing a composite biological patch according to claim 1, characterized in that, The fiber layer is a woven structure membrane material, an electrospun structure membrane material, or a cell-free dermal matrix membrane material of the same or different types. In the composite biological patch, the number of fiber layers is one or more.

3. The method for preparing a composite biological patch according to claim 2, characterized in that, The woven structure membrane material is selected from at least one of polypropylene, ultra-high molecular weight polyethylene, polylactic acid, polycaprolactone, and polyethylene terephthalate. The electrospun structural membrane material is a fiber structure formed by electrospinning technology using at least one of polylactic acid, polycaprolactone, collagen, silk fibroin, chitosan, and polyglycolic acid.

4. The method for preparing a composite biological patch according to claim 1, characterized in that, The matrix layer slurry is at least one of collagen solution, silk fibroin solution, gelatin solution, and decellularized dermal matrix microfiber solution.

5. The method for preparing a composite biological patch according to claim 4, characterized in that, The collagen solution, silk fibroin solution, and gelatin solution are prepared by dissolving collagen, silk fibroin, and gelatin in water or an aqueous acetic acid solution, respectively. The method for preparing the decellularized dermal matrix microfiber solution is as follows: the decellularized dermal matrix collagen membrane is soaked in an aqueous acetic acid solution, the soaked collagen membrane is mixed with water and mechanically broken to obtain microfibers, which are then filtered through a 200-400 mesh sieve to obtain the decellularized dermal matrix microfiber solution.

6. The method for preparing a composite biological patch according to claim 5, characterized in that, The acetic acid aqueous solution contains acetic acid with a mass fraction of 0.05% to 2.0%. The mass fraction of solute in the matrix layer slurry is 0.1% to 5.0%.

7. The method for preparing a composite biological patch according to claim 1, characterized in that, The freezing temperature is -50℃ to -1℃, and the freezing time is 8 to 48 hours; The freeze-drying temperature is -50℃ to -80℃, and the freeze-drying time is 24 to 72 hours.

8. The method for preparing a composite biological patch according to claim 7, characterized in that, The freezing temperature is -30℃ to -1℃, and the freezing time is 16 to 30 hours. The freeze-drying temperature is -65℃ to -80℃, and the freeze-drying time is 30 to 60 hours.

9. The method for preparing a composite biological patch according to claim 1, characterized in that, The freezing temperature is a gradient cooling method, and the freezing process is -1~-2℃ for 1~5h; -3~-15℃ for 2~15h; -16~-50℃ for 5~28h.

Citation Information

Patent Citations

  • Vacuum infusion processing method

    CN105150555A

  • Three-dimensionally woven composite prosthesis and production method thereof

    CN105641751A

  • Polymeric net-shaped composite patch

    CN113621247A

  • Surgical composite bionic patch

    CN219185109U